2021
DOI: 10.3390/plants10102115
|View full text |Cite
|
Sign up to set email alerts
|

A Novel QTL for Resistance to Phytophthora Crown Rot in Squash

Abstract: Phytophthora capsici Leonian causes significant yield losses in commercial squash (Cucurbita pepo) production worldwide. The deployment of resistant cultivars can complement integrated management practices for P. capsici, but resistant cultivars are currently unavailable for growers. Moderate resistance to Phytophthora crown rot in a selection of accession PI 181761 (C. pepo) (designated line #181761-36P) is controlled by three dominant genes (R4, R5 and R6). Introgression of these loci into elite germplasm th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…While several sources of resistance to Phytophthora crown rot [7][8][9][10][11] and their associated inheritance mechanisms [8,12] and QTLs [13][14][15] have been described in Cucurbita spp., the molecular mechanisms and gene pathways underlying the resistance remain poorly understood. In the current study, RNA sequencing revealed gene expression patterns in resistant and susceptible genotypes of Cucurbita following P. capsici infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While several sources of resistance to Phytophthora crown rot [7][8][9][10][11] and their associated inheritance mechanisms [8,12] and QTLs [13][14][15] have been described in Cucurbita spp., the molecular mechanisms and gene pathways underlying the resistance remain poorly understood. In the current study, RNA sequencing revealed gene expression patterns in resistant and susceptible genotypes of Cucurbita following P. capsici infection.…”
Section: Discussionmentioning
confidence: 99%
“…In both C. moschata (breeding line #394-1-27-12 carrying resistance from C. lundeliana) and C. pepo (breeding line #181761-36P), resistance to Phytophthora crown rot is conferred by three independent dominant genes [8,12]. Furthermore, the quantitative trait loci (QTLs) associated with resistance to Phytophthora crown rot have recently been reported in C. moschata [13] and C. pepo [14,15], paving the way for the application of marker-assisted selection in germplasm improvement. However, despite these advancements, the molecular mechanisms underlying resistance to Phytophthora crown rot are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%